RETRACTED: Floating export duties as a tool for state regulation of the Russian grain market - S. G. Serikov (Вестник университета)
RETRACTED ARTICLESince mid-2021, Russia has applied floating export duty (damper) as a mechanism for state regulation of grain market. The results of the study have showed that introduction of damper as an instrument of state regulation of the Russian grain market has only exacerbated the problems associated with the growing volatility of grain prices and their increasing dependence on the global market environment. In addition, the mechanism of redistributing funds received by the state from export duties and allocated to grain producers in the form of subsidies remains opaque and incomprehensible. The transition from dollar to rubles in duty calculations has shown the viability of this method, hence the current practice is worth continuing in order to make the mechanism for distributing subsidies to grain producers from export duties received completely transparent and understandable. Thus, the operation of grain damper is economically justified only if the state is ready to support the grain market in proportion to this sector contribution to the national economy development.